Interleukin-13 receptor α2 is associated with poor prognosis in patients with gastric cancer after gastrectomy - Lin, Chao (Oncotarget, 2016)
BACKGROUND: Interleukin-13 receptor α2 (IL-13Rα2) plays a vital role in the invasion and metastasis of various types of cancer, but its role in prognosis of patients with gastric cancer remains unknown. The aim of this study was to investigate the impact of IL-13Rα2 expression on the prognostic value in gastric cancer patients after surgery. RESULTS: Increased expression of IL-13Rα2 in tumoral tissue was associated with decreased overall survival rate (P < 0.001). IL-13Rα2 expression was an independent prognostic indicator for gastric cancer (P < 0.001). Stratification analyses showed IL-13Rα2 expression could give some additional prognostic information in tumors of different stages, especially in advanced tumors. Integrating IL-13Rα2 expression with generated a better nomogram that was validated by the validation set to predict the 5-year overall survival. METHODS: IL-13Rα2 expression was evaluated by tissue microarrays from 507 gastric cancer patients from two academic medical centers and statistically assessed for correlations with the clinical profiles and the prognosis of the patients with gastric cancer. The prognostic nomogram was designed to predict 5-year overall survival probability. CONCLUSIONS: IL-13Rα2 expression might be an independent prognostic factor for gastric cancer after surgical resection and could potentially be a high-priority therapeutic target. Incorporating IL-13Rα2 expression into the TNM staging system can provide a good prognostic model.